COMPETITIVENESS OF POLISH AGRI-FOOD EXPORTS IN CENTRAL ASIA IN 2019-2023 - Małgorzata Bułkowska (Annals of the Polish Association of Agricultural and Agribusiness Economists)
Since Russia’s invasion of Ukraine in February 2022, the European Union has revised its approach to Central Asia, becoming increasingly engaged in promoting regional stability and leveraging the region’s potential as a transport corridor linking Europe and China while bypassing Russia. Poland, as a major food producer within the EU, has emerged as a key partner in EU-Central Asia relations due to its geographic location. The aim of this study is to assess changes in trade flows and the competitiveness of Polish agri-food exports to Central Asia between 2019 and 2023. Three indicators are used: the Revealed Symmetric Comparative Advantage index (RSCA), the Trade Balance Index (TBI), and the Export Share Index (ESI). Based on RSCA and TBI, a matrix was constructed to provide a synthetic assessment of the competitiveness of Polish agri-food products in Central Asian markets. The results indicate that between 2019 and 2023, Central Asian countries significantly increased their imports of agri-food products from the EU, with Poland accounting for 16.6% of these exports—the highest share among EU member states. The indicator-based analysis shows that Polish exports to Central Asia were dominated by products for which Poland exhibited both a comparative advantage and a trade surplus. These included fruit and vegetables, processed fruit and vegetable products, cereal products and pastries, animal waste and feed, live plants, as well as meat and offal. The study contributes to the literature by evaluating the formation of Poland’s comparative advantages in the Central Asian market, thereby addressing a notable research gap.